2004
DOI: 10.1007/s00330-004-2260-1
|View full text |Cite
|
Sign up to set email alerts
|

Actual clinical use of gadolinium-chelates for non-MRI applications

Abstract: For many years, alternatives to iodinated X-ray contrast media have been sought. Of the contrast media investigated to date, only CO(2) and the gadolinium-chelates have been shown to be viable alternatives for selected X-ray examinations. Therefore, we have reviewed the general literature and that specific for gadopentetate (Magnevist) in particular, since this agent has been studied the most. This review indicates that diagnostic CT examinations can be achieved following the intravenous administration of gado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 54 publications
0
36
1
2
Order By: Relevance
“…Thus, a gadolinium (Gd) CM may be used as an x-ray CM. Before the advent of nephrogenic systemic fibrosis (NSF) (Thomsen, 2009), some investigators reported on the use of Gd-CM in a variety of diagnostic angiographic and interventional procedures (Spinosa et al, 2002;Strunk & Schild, 2004) including PCA (Barcin et al, 2006;Briguori et al, 2006;Gupta & Uretsky, 2005;Sarkis et al, 2003;Voss et al, 2004) in patients at risk of CIN due to its perceived non-nephrotoxicity (Prince et al, 1996). However, the non-nephrotoxicity of Gd-CM has been proved wrong (Buhaescu & Izzedine, 2008;Ergun et al, 2006;Sam et al, 2003).…”
Section: Iodine Concentration Iso-attenuating With Gadolinium CMmentioning
confidence: 99%
“…Thus, a gadolinium (Gd) CM may be used as an x-ray CM. Before the advent of nephrogenic systemic fibrosis (NSF) (Thomsen, 2009), some investigators reported on the use of Gd-CM in a variety of diagnostic angiographic and interventional procedures (Spinosa et al, 2002;Strunk & Schild, 2004) including PCA (Barcin et al, 2006;Briguori et al, 2006;Gupta & Uretsky, 2005;Sarkis et al, 2003;Voss et al, 2004) in patients at risk of CIN due to its perceived non-nephrotoxicity (Prince et al, 1996). However, the non-nephrotoxicity of Gd-CM has been proved wrong (Buhaescu & Izzedine, 2008;Ergun et al, 2006;Sam et al, 2003).…”
Section: Iodine Concentration Iso-attenuating With Gadolinium CMmentioning
confidence: 99%
“…For the tissue targets, liver, spleen, lymph nodes and the blood pool, efficient contrast-enhancing compounds have been described that utilize different active transport systems or passive diffusion-limiting molecular sizes. The agents include water-soluble metal chelates (122)(123)(124), iodinated polymeric compounds, and contrast-agent-carrying liposomes (125)(126)(127).…”
Section: Contrast Agents Molecular Probes and Tracersmentioning
confidence: 99%
“…In the clinics, correlative studies using combinations of imaging methods, most notably MR and CT imaging, are often performed on the same patient to improve the accuracy of diagnosis or assess the efficacy of treatment routines. For instance, commercially available gadolinium-containing MR agents have been used for CT imaging, but limitations associated with the dosage and costs have prevented their widespread use (123,124). Liposomebased multimodal contrast agents for CT and MRI with prolonged contrast enhancement in vivo have been proposed for cardiovascular imaging as well as image registration and guidance applications in radiation therapy (146).…”
Section: Contrast Agents For Multimodality Imagingmentioning
confidence: 99%
“…Gadolinium contrast media (Gd-CM), primarily intended for magnetic resonance imaging (MRI), are regarded by many as a less or even non-nephrotoxic alternative to iodine CM (I-CM) in patients with renal impairment undergoing x-ray angiography (XRA), and computed tomography (CT) [1][2][3][4][5][6][7][8], though this view has no scientific support. There are no human studies comparing their nephrotoxic effects at volumes and concentrations resulting in the same x-ray attenuation [9,10].…”
Section: Introductionmentioning
confidence: 99%